Internet connectivity disruption in DR Congo (DR Congo) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in DR Congo. Data sourced from IODA.
Network Disruption Incident ID: CD-2026-0044. Severity: critical. Confidence: 65%